1998
DOI: 10.1073/pnas.95.26.15724
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cβ4 is specifically involved in climbing fiber synapse elimination in the developing cerebellum

Abstract: Elimination of excess climbing fiber (CF)-Purkinje cell synapses during cerebellar development involves a signaling pathway that includes type 1 metabotropic glutamate receptor, G␣q, and the ␥ isoform of protein kinase C. To identify phospholipase C (PLC) isoforms involved in this process, we generated mice deficient in PLC␤4, one of two major isoforms expressed in Purkinje cells. PLC␤4 mutant mice are viable but exhibit locomotor ataxia. Their cerebellar histology, parallel fiber synapse formation, and basic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 178 publications
(171 citation statements)
references
References 37 publications
8
163
0
Order By: Relevance
“…Further confirmation and extension of these findings came from studies showing that a perturbation of the mGluR1-activated signaling cascade at virtually every level [e.g., G-protein G␣q (Offermanns et al, 1997), phospholipase C␤ (Kano et al, 1998), and IP 3 (Matsumoto et al, 1996;Miyata et al, 2000)] results in impaired LTD and disturbed cerebellar motor control. IP 3 causes Ca 2ϩ release from intracellular stores (Mikoshiba et al, 1994;Finch and Augustine, 1998;Takechi et al, 1998), and synaptically induced dendritic Ca 2ϩ signaling has been known for a long time to be a critical step in LTD induction (Sakurai, 1990;Konnerth et al, 1992).…”
Section: Introductionmentioning
confidence: 73%
“…Further confirmation and extension of these findings came from studies showing that a perturbation of the mGluR1-activated signaling cascade at virtually every level [e.g., G-protein G␣q (Offermanns et al, 1997), phospholipase C␤ (Kano et al, 1998), and IP 3 (Matsumoto et al, 1996;Miyata et al, 2000)] results in impaired LTD and disturbed cerebellar motor control. IP 3 causes Ca 2ϩ release from intracellular stores (Mikoshiba et al, 1994;Finch and Augustine, 1998;Takechi et al, 1998), and synaptically induced dendritic Ca 2ϩ signaling has been known for a long time to be a critical step in LTD induction (Sakurai, 1990;Konnerth et al, 1992).…”
Section: Introductionmentioning
confidence: 73%
“…In early post-natal days, all Purkinje cells are innervated by multiple climbing fibres (multiple innervation) Crepel 1982;Lohof et al 1996). These surplus climbing fibres are eliminated eventually with the progress of post-natal development, and most Purkinje cells become innervated by single climbing fibres (mono-innervation) by the end of the third post-natal week in mice (Kano et al , 1998Offermanns et al 1997).…”
Section: Synapse Eliminationmentioning
confidence: 99%
“…Kano, Hashimoto and co-workers show that the mutant mice deficient in mGluR1, G aq , PLCb4 or PKCg are all impaired in climbing fibre synapse elimination (Kano et al , 1998Offermanns et al 1997;Hashimoto et al 2000Hashimoto et al , 2001bIchise et al 2000). Levenes et al (1997) also reported incomplete synapse elimination in the mGluR1 knockout mice.…”
Section: Synapse Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…CF elimination consists of two distinct phases in mice, the early phase from P7 and the late phase from around P12 (12), which involve distinct mechanisms (9,12). Whereas several factors crucial for the late phase of CF synapse elimination have been disclosed (13)(14)(15)(16)(17)(18)(19)(20), mechanisms of biased strengthening of single CFs and the early phase of CF synapse elimination are unknown. Because synapse refinement critically depends on neuronal activity (1,4,5,16,21,22), we studied whether the P/Q-type voltage-dependent Ca 2+ channel (VDCC), the major high-threshold VDCC in PCs (23), is involved in the development of CF to PC synapses.…”
mentioning
confidence: 99%